Systematic Review and Meta-Analysis: Online and Blended Learning Workshop - Linda Meurer (Association of American Medical Colleges, 2008)
Abstract This resource is a two-part, web-based introductory workshop on interpretation and conduct of meta-analyses. Initially developed as part of a master's-level epidemiology course on a variety of research methods, the module can be used to introduce medical students, residents, fellows, and junior faculty to the systematic review of literature. The first part includes an introductory slide-show overview, a link to the user's guide to the literature module for systematic reviews, and an assignment to apply a validity worksheet to several published reviews. The second part walks students through the steps of a systematic review, including articulating an answerable question, establishing study inclusion criteria, conducting a search, unbiased selection of relevant articles, extraction of data, validity assessment, and summary risk estimation using review manager software. While both parts can be completed as self-study modules, part II is designed to be presented as a blended learning module with facilitation by an instructor. Thus far, the course has been presented to two classes of epidemiology graduate students (mostly clinical postdoctoral fellows) and has been used as a tutorial for several summer research students as an introduction prior to their own meta-analysis projects. The course has been well received, and participants have been highly engaged. Respondents to an evaluation described the course as easy or very easy to navigate and agreed that objectives were definitely or mostly met. Following the course, 74% reported that they were somewhat likely or highly likely to conduct a meta-analysis in the future. Specific lessons learned are included in the instructor's guide. The materials included here are limited to references; users will need to obtain access to relevant articles for their learners in accordance with copyright laws.